Microwave Rectifier untuk Transmisi Listrik Tanpa Kabel dengan Metode Matching Impedance - Wahyu Hendra Gunawan; Fitri Oktafiani; Deryanto Balalembang (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2018)
In this modern era, the high consumption of electrical energy requires considerable resources. Resources used in this modern era include non-renewable energy and environmentally unfriendly, so it takes a new method that is environmentally friendly to meet the needs of electric energy consumption. The energy harvesting technique comes as an environmentally friendly source of energy, harvesting energy techniques utilize the resources around us without causing waste and pollution. Rectifier with matching impedance as a wireless power transmission with signal rectifier capability is an environmentally friendly method of energy harvesting technique. Rectifiers can generate electrical energy sources by utilizing electromagnetic waves as resources captured by antennas. Rectifiers are designed with application simulation process, matching impedance calculation, design printing and measurement with special measuring instrument. Rectifiers are designed and realized in the form of full-wave rectifier types. This rectifier uses a schottky diode HSMS 2860, The measurement of rectifier that uses a signal generator as a measuring device generated output of 5.08 V at 2.4 Ghz level +20 dBm and return loss -37.70 dBm at 2.4 Ghz level +5 dB. Keywords: Microwave, Rectifier and Matching Impedance